Penerapan Strategi Pembelajaran Peningkatan Kemampuan Berpikir (SPPKB) Peserta Didik untuk Meningkatkan Hasil Belajar Matematika pada Materi Trigonometri di Kelas X-1 SMA Negeri 1 Hibala TP.2022/2023 - Titus Bago (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2024)
The aim of this research is to determine the improvement in mathematics learning outcomes in Trigonometry material through the application of learning strategies to improve thinking skills (SPPKB) for students in Class X of SMA Negeri 1 Hibala. This research was conducted in Class X of SMA Negeri 1 Hibala, with a collaborative class action research design. This classroom action research is carried out in the form of an iterative cycle in which there are four main stages of activity, namely planning, action, observation and reflection, and so on until the expected improvements or improvements are achieved. Based on the results of the research that has been carried out, it can be concluded that the application of learning strategies to improve students' thinking skills (SPPKB) can improve the mathematics learning outcomes of students in Class X of SMA Negeri 1 Hibala. Improved student learning outcomes can be seen from the test results at the end of each meeting. The results of this research prove that there is an increase in student learning outcomes as follows. In cycle I, meeting-1, there was an increase, namely from the average score before the action of 65.37, in other words, the percentage of students' learning completeness was 37.50% to 70.12 or the percentage of students' learning completeness was 40.50%; then at meeting 2 it increased to 75.25 or the percentage of students' learning completeness was 67.50%. In cycle II, meeting-1, there was still an increase from the average value of cycle I, meeting-2, namely from 75.25 to 77.00 or the percentage of students' learning completeness, which was 75%, then at meeting-2 the average value of the class increased to 81.12, in other words, the percentage of students' mathematics learning completeness is 82.50%.